Addressing the growing burden of obesity, diabetes and asthma in children and adolescents: The role of primary health care and the WHO Pocket book in Europe for a healthy future - Sophie Jullien; Susanne Carai; Martin W. Weber (Elsevier, 2024)
The burden of obesity, diabetes mellitus and asthma remains a significant public health issue worldwide. These conditions are associated with premature deaths and a reduced quality of life. Primary health care plays a key role in the prevention, detection, and management of noncommunicable diseases in childhood, including diabetes and asthma. Health promotion is crucial for a healthy life from early childhood, preventing from obesity, a sedentary lifestyle, exposure to tobacco smoke, and other risk factors associated to noncommunicable diseases. Asthma and type 1 diabetes mainly begin in childhood; thus, recognition and early detection at the primary health care level are essential. In the long term, management of children with chronic diseases requires regular follow-up and cooperation with a specialized team. Care coordination by the primary health care provider is key for optimal control of the disease and development of the child or adolescent in the physical, emotional, and social spheres. Over-referral for diagnosis and follow-up is associated with unnecessary specialist overload, patient anxiety, and financial burden for the families and the health system. Clear criteria and referral pathways with efficient communication between the professional team members are essential to empower primary health care providers, avoid unnecessary referrals, and optimize the care and quality of life of children and adolescents with chronic diseases.The WHO Pocket book of primary health care for children and adolescents was recently developed to address knowledge gaps and improve the diagnosis and management of children and adolescents at the outpatient level. It dedicates an entire chapter to health promotion and disease prevention with counselling messages addressed to children, adolescents and their families; provides guidance for the diagnosis and management of asthma, diabetes and other chronic diseases; and includes additional considerations for adolescents living with chronic conditions.